Control and empowerment as an organising paradox: implications for management control systems. Issue 2 (31st May 2019) - Lewis, Rachael L.; Brown, David A.; Sutton, Nicole C.
Abstract : Purpose: The purpose of this paper is to reframe the debate about the tension between management control and employee empowerment by drawing on a theory of paradox. Reframing the problem in this way draws attention to the variety of ways in which organisations can attend to both control and empowerment simultaneously. Design/methodology/approach: The authors undertake a conceptual examination of the relationship between empowerment and control using a paradox theory lens. First, the authors bring together two dimensions of empowerment – structural empowerment and psychological empowerment – and combine them to produce three new empowerment "scenarios": illusory empowerment, obstructed empowerment and authentic empowerment. For each of these three scenarios, the central tenets of paradox theory are applied in order to explain the nature of the paradoxical tension, anticipated behavioural responses and the resulting challenges for ongoing management control. Findings: The authors find that neither structural nor psychological empowerment alone can account for variation in behavioural responses to management control. The conceptual analysis highlights the interplay of socio-ideological control and systems of accountability in generating psychological empowerment and demonstrates that this does not come at a cost to management control but instead results in a reduction in the scale and scope of ongoing challenges. Originality/value: This paper contributes a new theoretical perspective on the classic problem of tension between management control and employee empowerment. Rather than positioning control and empowerment either as a managerial choice or dialectic, the authors identify three different ways in which organisations can engage with both paradoxical elements simultaneously.